KORELASI MINAT MEMBACA DAN PENGUASAAN KOSAKATA TERHADAP KEMAMPUAN MENULIS NARASI SISWA KELAS VIII SMP DI KECAMATAN SEBERANG ULU PALEMBANG - Khairunnisa Khairunnisa; Didi Suhendi (Jurnal Pembahsi (Pembelajaran Bahasa Dan Sastra Indonesia), 2017)
Abstract: This study aims to determine whether there is a correlation between (1) reading and narrative writing skills, (2) vocabulary and narrative writing skills, (3) interest in reading and vocabulary together with the ability to write narrative. The sample in this study were 256 students. Sampling using simple random sampling technique. Variables studied that interest in reading, vocabulary and writing skills narration. Questionnaires use traditional data collection techniques and tests. The results show that (1) there is a significant relationship between reading and writing skills of narrative students, (2) a significant relationship between vocabulary and writing skills of narrative, and (3) the existence of a positive relationship between reading and vocabulary with the ability to write narrative. From these results it can be stated that together reading and vocabulary contribute to students' ability to write narrative.